Accurate Orientation of the t-Branch Off-the-Shelf Multibranched Endograft After Deployment in Urgent Cases. (August 2018) - Spanos, Konstantinos; Theodorakopoulou, Myrto; Debus, E. Sebastian; Rohlffs, Fiona; Heidemann, Franziska; Kölbel, Tilo; Tsilimparis, Nikolaos
Purpose: To evaluate the orientation of the standardized off-the-shelf multibranched t-Branch after implantation in urgent thoracoabdominal aortic aneurysm (TAAA) repairs, to characterize the impact of branch malorientation on procedural success, and to identify any predictive factors associated with malorientation.Methods: A retrospective analysis was conducted of 42 consecutive patients (mean age 73.3±7 years; 25 men) with urgent TAAA presentation treated with the t-Branch from January 2014 to June 2017. The primary objective was to quantify the preoperative clock position of the target vessels and determine any rotational deviation between the pre- and postoperative measurements and between the postoperative measurements and the standard branch configuration. Secondary outcomes were to identify factors influencing malorientation (>2 clock face hours) that could affect outcome. Results were compared for early (learning curve; n=18) vs late (n=24) experience and for adherence to (n=23) vs nonobservance of (n=19) the instructions for use (IFU).Results: Technical success was 93% (39/42). No significant difference in rotational deviation was identified between patients treated within the IFU vs outside the IFU. Seven (17%) patients had at least one target vessel maloriented after the procedure, which was not associated with total procedure time, fluoroscopy time, contrast volume, radiation dose, or adherence to the IFU. Female gender was associated with increased rotational deviation in postprocedure measurement for the celiac trunk (p=0.044) and superior mesenteric artery (SMA; p=0.006). Female gender was also associated with increased rotational deviation between the branch origin after deployment and the standard configuration of the t-Branch for every target vessel [celiac trunk (p=0.005), SMA (p=0.001), right renal artery (p=0.037), and left renal artery (p=0.003)].Conclusion: The implantation of the t-Branch device in urgent cases achieved accurate apposition without rotational deviation between the target vessels and the position of the endograft branches. Gender may have an impact on orientation of the device. The t-Branch appears to have a "forgiving" nature for higher malorientation with no effect on procedure time, target vessel revascularization, or early branch patency.